Estrogen modulates expression of the glycosyltransferases that synthesize sulfated oligosaccharides on lutropin. - Dharmesh, S M (1993)
The glycoprotein hormone lutropin (LH) bears oligosaccharides terminating with the sequence SO4-4-GalNAc beta 1,4GlcNAc beta 1,2 Man alpha. We have determined that estrogen actively modulates expression of the GalNAc- and sulfotransferases responsible for synthesis of sulfated oligosaccharides on LH alpha and beta subunits. Consequently, terminal glycosylation of LH oligosaccharides with GalNAc-4-SO4 is maintained when LH synthesis and secretion are markedly increased, as occurs during the midcycle surge and following ovariectomy. Maintenance of sulfated oligosaccharides on LH has important biologic consequences because LH circulatory half-life as well as biologic activity at the hormone receptor level are dramatically affected by glycosylation. To our knowledge, regulation of glycosyltransferase levels in response to specific stimuli has not been observed previously, further emphasizing the biologic significance of glycosylation for expression of LH bioactivity in vivo.